2021
DOI: 10.3390/cancers13164095
|View full text |Cite
|
Sign up to set email alerts
|

Smart Modification on Magnetic Nanoparticles Dramatically Enhances Their Therapeutic Properties

Abstract: Magnetic nanoparticles (MNP) are employed as nanocarriers and in magnetic hyperthermia (MH) for the treatment of cancers. Herein, a smart drug delivery system composed of MNP functionalized with the cytotoxic drug gemcitabine (MNP-GEM) has been thoroughly evaluated. The linker employed is based on a disulfide bond and allows the controlled release of GEM under a highly reducing environment, which is frequently present in the cytoplasm of tumor cells. The stability, MH, and the interaction with plasma proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
(107 reference statements)
0
13
1
Order By: Relevance
“…A cell viability assay revealed that the toxicity of our nanoformulation of DIO-NPs starts with a dose of 42 μg/mL reaching a 50% reduction in cell metabolic activity at a dose of 56 μg/mL (1 mM) of DIO-NPs after 72 h. Different from our results, Lafunete-Gomez et al (2021) [ 46 ] indicated that dextran-coated ɣ-Fe 2 O 3 NPs with a larger size (of around 100 nm) caused no toxicity in PANC-1 cells up to a concentration of 2 mg Fe/mL after 72 h. Another study showed that, without affecting cell viability, dextran-coated ɣ-Fe 2 O 3 NPs of about 75 nm cause oxidative stress and genotoxicity at a dose of 4 μg/mL after 24 h [ 47 ]. In this regard, further research will be necessary to determine an exact time frame for the clearance of DIO-NPs by the reticuloendothelial system (RES) in vivo in order to prove their cytotoxicity on pancreatic cells.…”
Section: Discussioncontrasting
confidence: 99%
“…A cell viability assay revealed that the toxicity of our nanoformulation of DIO-NPs starts with a dose of 42 μg/mL reaching a 50% reduction in cell metabolic activity at a dose of 56 μg/mL (1 mM) of DIO-NPs after 72 h. Different from our results, Lafunete-Gomez et al (2021) [ 46 ] indicated that dextran-coated ɣ-Fe 2 O 3 NPs with a larger size (of around 100 nm) caused no toxicity in PANC-1 cells up to a concentration of 2 mg Fe/mL after 72 h. Another study showed that, without affecting cell viability, dextran-coated ɣ-Fe 2 O 3 NPs of about 75 nm cause oxidative stress and genotoxicity at a dose of 4 μg/mL after 24 h [ 47 ]. In this regard, further research will be necessary to determine an exact time frame for the clearance of DIO-NPs by the reticuloendothelial system (RES) in vivo in order to prove their cytotoxicity on pancreatic cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the silica chemistry facilitates the easy attachment of functional molecules-especially those bearing amine of carboxyl groups-thus adding new functionalities to the hybrid nanostructures, such as fluorescence [29][30][31] and therapeutic [31][32][33] and catalytic functions [34]. As it was recently demonstrated, the attachment of a chemotherapeutic agent to the MNPs, reduced the cytotoxic effect of the drug in non-cancerous cells, improved the internalization in cancer cells, and its activity was synergistically enhanced in combination with magnetic hyperthermia [35]. Thus, the controlled encapsulation of the MNPs in a silica shell, by preserving their magnetic properties, enhancing their biocompatibility, and increasing their ability for functionalization with various functional groups represents a huge potential for future clinical translation of the MH technique.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nanocarriers can release their therapeutic cargo in a stable and controlled manner. A plethora of stimuli, such as changes in pH, redox, temperature, or magnetic forces, can trigger the release of drugs by evoking a change in the structures of the nanocomplex, to ensure toxicity exclusively into target tissue, without affecting healthy tissues [219].…”
Section: Nanomedicine May Increase the Potential Of Drugs Modulating Autophagymentioning
confidence: 99%